A complex role of chromogranin A and its peptides in inflammation, autoimmunity, and infections - Maj, Maciej; Hernik, Karolina; Tyszkiewicz, Kaja; Owe-Larsson, Maja; Sztokfisz-Ignasiak, Alicja; Malejczyk, Jacek; Janiuk, Izabela (Frontiers in Immunology, 2025)
Chromogranin A (CgA), mostly known as a nonspecific neuroendocrine tumor marker, was the first glycoprotein from the granin family characterized as a prohormone for various bioactive peptides including vasostatin I/II (VS-I, VS-II), catestatin (CST), chromofungin (CHR), pancreastatin (PST), WE-14, and others. CgA and its derivatives present various functions, often antagonistic, in maintaining body homeostasis and influencing the immune system. This review aims to summarize the not fully understood role of CgA and its derivatives in inflammation, autoimmunity, and infections. CgA seems to be involved in the complex pathophysiology of cardiovascular disorders, neurodegenerative diseases, and other conditions where immune system dysfunction plays a role in the onset and development of the disease (e.g. systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD), or rheumatoid arthritis (RA)). However, the direct immunomodulatory role of CgA is difficult to assess since many of its activities may be linked with its peptides. CST and VS-I are considered anti-inflammatory molecules, due to M2 macrophage polarization stimulation and downregulation of certain proinflammatory cytokines. Conversely, PST is reported to stimulate proinflammatory M1 macrophage polarization and Th1 lymphocyte response. Thus, the final effects of CgA in inflammation may depend on its cleavage pattern. Additionally, peptides like CST, VS-I, or CHR exert direct antimicrobial/antifungal activities. CgA, WE-14, and other less-known CgA-derived peptides have also been reported to trigger autoimmune responses, highly studied in type 1 diabetes mellitus. Overall, CgA and its derivatives have an interesting but complex role in immunity, however, their specific roles require further research.